Effectiveness of the Use Module Handling Emergency Retention Plasenta in Training on Midwive Attitude - Dewi Yanti (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Midwives telatih more appreciated, more confident and capable of behaving with incidents obstetric complications. [1] When the knowledge and attitude of a midwife is low, the possibility of vaginal birth and treatment of complications is difficult. [2] Less than optimal attitude for the officers acted appropriately, and the fear and confusion attendant identified as a major obstacle in providing obstetric care services. [3] Pregnant women complained that the assistance they received during labor is not adequate and questioned about the attitude and competence of midwives and doctors that address. [4] Necessary efforts to overcome the lack of adequate attitude in handling obstetric emergency personnel including retained placenta. Optimizing retrieval capability right attitude and immediately, Thought to beone with learning enhanced through training modules. This enelitian create a simple module modified with an algorithm on the front cover. In order to guide the midwife in making the proper attitude and immediately if encountered the case of retained placenta. expected to avoid mishandling and delays in handling Refer. Objective Knowing the effective use of retained placenta emergency handling module on the attitudes midwife training and development modules. Method Experiment study randomized trial control group pretest-posttest design approach with a questionnaire. The independent variable use emergency handling module placenta in training. The dependent variable attitudes midwife. Confounding variables: age, length of employment, education, and experience retained placenta menanangani Population: midwife in the community in seven health centers and a sample of 50 participants. Results The use of retained placenta emergency handling module on training, Effectively improve the attitude of 0.63 points (95% CI 0.46-0.79) p = 0.001, an increase of 45.82%.